"--- Tamen a una spia fuori ---" - Pust, Klemen (Acta Histriae, 2008)
The paper discusses intelligence activities of the Venetian Republic and their significance and range in the Adriatic region during the year 1499. The main source used were the notes in the Diaries (I Diarii) by the Venetian councillor Marino Sanudo, perhaps representing the single most important source covering this topic in this time period. Apart from this document and relevant scientific literature some other published and unpublished documents were used. The year 1499 was chosen due to the general significance of events taking place during this year in the region discussed. That was the time of the last Ottoman invasion of Friuli in the heart of the Venetian mainland, taking place during the first year of the Venetian-Ottoman War (1499-1502). This very military combat was the last one wherein both sides engaged in intensive warfare throughout the entire Adriatic region as well as the Venetian mainland. At the same time it represented an acknowledgement of the Ottoman military success in the Balkans by the Venetians and a confirmation of the Venetian abatement politics with occasional straining of relations with the Ottoman empire, characterizing the Venetian foreign policy in the following centuries and lasting until the decline of both superpowers. During the year 1499 the Venetian Republic closely monitored the events taking place in the Adriatic estates through a wide network of intelligence operatives, established in this important region, which represented a transition zone for large-scale Ottoman invasions towards Friuli in the immediate hinterland of Venice. The reports of intelligence operatives provided detailed and timely information concerning Ottoman military and political maneuvers, including the invasion of Friuli. Croatian noble families, which were coerced into constant combat with the Ottoman army or were even forced from their territories, played a considerable role within this intelligence network. Venetian authorities established centres for gathering the information of intelligence operatives from the Adriatic in Friuli in the Udine and Cividale, where information from nearby as well as more distant Venetian estates in Istria and particularly in Dalmatia was accumulated. In the Adriatic region, the two main centres for gathering intelligence were established in Zadar and Koper, which were regarded as the capitols of Dalmatia and of Istria, respectively. Venetian officials from small settlements would send their intelligence reports to superintendents of Zadar and Koper and in turn this information was sent on to Venice. As was the case in the Hapsburg realm, in the Venetian Republic a very important role in the intelligence network was played by military officers, regional superintendents and field officials, though normally the highest authorities were made aware of intelligence reports in all cases as well.
Keywords: Beneška republika; Croatia; Hrvaška; obveščevalna dejavnost; osmanski vpadi; plemiške rodbine; Republic of Venice; vzhodni Jadran